PENGEMBANGAN ASESMEN PEMBELAJARAN BERBANTUAN APLIKASI QUIZIZZ PADA IPAS MATERI INDONESIAKU KAYA BUDAYA KELAS IV SD - Novita, Dina Sri; Beta Rapita Silalahi; Sutikno; Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning assessment assisted by the Quizizz application for the IPAS subject with the topic My Indonesia, Rich in Culture for fourth-grade elementary school students. The background of this research is the low level of student engagement in assessments, which remain conventional and lack the use of technology. This study employs Research and Development (R&D) methodology using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The assessment product was developed based on the learning outcomes of the Merdeka Curriculum and validated by content experts, assessment experts, instructional experts, and tested on fourth-grade students at SD Negeri 064034 Medan Johor. The validation results showed that the developed assessment was considered feasible before revision (78%) and became very feasible after revision (84%). Additionally, the assessment received a 88% feasibility rating from the assessment expert, 98% from the instructional expert, and 94.82% positive responses from students. These findings indicate that the Quizizz application is effective as an interactive and engaging assessment tool, and can enhance students' interest and understanding of Indonesia’s cultural diversity.